2005
DOI: 10.1261/rna.2670705
|View full text |Cite
|
Sign up to set email alerts
|

Unrestricted accessibility of short oligonucleotides to RNA

Abstract: The propensity of RNA to fold into higher-order structures poses a major barrier to the use of short probes (<15 nucleotides) by preventing their accessibility. Introduction of the pseudo-complementary bases 2-aminoadenine (nA) and 2-thiouracil (sU) and the destabilizing base 7-deazaguanine (cG) into RNA provides a partial solution to this problem. While complementary in hydrogen bonding groups, nA and sU cannot form a stable base pair due to steric hindrance, and are thus pseudo-complementary. Each, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Consistent with these properties, DNA substituted with cG exhibits fewer banding artifacts in sequencing gels ( 23 ). Given our earlier success in using cG to reduce secondary structure in DNA and RNA that also contained nA and sT/sU ( 16 , 24 ), we evaluated analogs of cG substituted at the C7 position with alkyl or halo groups. Indirect evidence suggested that these modifications could modulate the pairing strength of cG ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these properties, DNA substituted with cG exhibits fewer banding artifacts in sequencing gels ( 23 ). Given our earlier success in using cG to reduce secondary structure in DNA and RNA that also contained nA and sT/sU ( 16 , 24 ), we evaluated analogs of cG substituted at the C7 position with alkyl or halo groups. Indirect evidence suggested that these modifications could modulate the pairing strength of cG ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…Strong pairing permits the use of short oligonucleotides so that self-folding of probe is largely avoided. Moreover, short oligonucleotides provide enhanced specificity of binding (10). Isoenergetic binding further simplifies interpretation of data because binding will be primarily dependent on target structure rather than probe sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The results described here represent a first step in evaluating pcONs as potential DNA targeting and gene repair agents. In all likelihood, eukaryotic recombinases will require the use of longer incoming pcDNAs and annealing pcRNAs that could be prepared, respectively, by asymmetric PCR or transcription ( 48 , 49 ). With increased size, double D-loop joints should form more readily and exhibit greater stability.…”
Section: Discussionmentioning
confidence: 99%